Inorganic Cation Transport and Energy Transduction in Enterococcus hirae and Other Streptococci - Kakinuma, Yoshimi (American Society for Microbiology, 1998)
Energy metabolism by bacteria is well understood from the chemiosmotic viewpoint. We know that bacteria extrude protons across the plasma membrane, establishing an electrochemical potential that provides the driving force for various kinds of physiological work. Among these are the uptake of sugars, amino acids, and other nutrients with the aid of secondary porters and the regulation of the cytoplasmic pH and of the cytoplasmic concentration of potassium and other ions. Bacteria live in diverse habitats and are often exposed to severe conditions. In some circumstances, a proton circulation cannot satisfy their requirements and must be supplemented with a complement of primary transport systems. This review is concerned with cation transport in the fermentative streptococci, particularly Enterococcus hirae. Streptococci lack respiratory chains, relying on glycolysis or arginine fermentation for the production of ATP. One of the major findings with E. hirae and other streptococci is that ATP plays a much more important role in transmembrane transport than it does in nonfermentative organisms, probably due to the inability of this organism to generate a large proton potential. The movements of cations in streptococci illustrate the interplay between a variety of primary and secondary modes of transport.